Investigation of Invigorating Qi and Activating Blood Circulation Prescriptions in Treating Qi Deficiency and Blood Stasis Syndrome of Ischemic Stroke Patients: Study Protocol for a Randomized Controlled Trial - Wang, Yu; Zhang, Ling; Pan, Yuan-jiang; Fu, Wei; Huang, Shu-wei; Xu, Bin; Dou, Li-ping; Hou, Qun; Li, Chang; Yu, Li; Zhou, Hui-fen; Yang, Jie-hong; et al. (Frontiers in Pharmacology, 2020)
Ischemic stroke (IS) is characterized by high morbidity and high mortality. Chinese herbal formulas combined with routine pharmacotherapy have shown promising benefits in relieving symptoms, promoting neurological recovery, and improving the quality of life in patients with IS. According to Traditional Chinese medicine (TCM) diagnosis, Qi-deficiency and blood-stasis (QDBS) syndrome is one of the common types of IS, which is treated by the method of invigorating Qi and activating blood circulation. In TCM theory, improve the corresponding degree of prescription-syndrome correlation (PSC) is helpful to improve the clinical efficacy. In this study, based on the concept of "precision medicine", we intend to use similar prescriptions of invigorating Qi and activating blood circulation, Buyang Huanwu granule (BHG), Naoxintong capsule (NXTC), and Yangyin Tongnao granules (YTG), to evaluate the level of PSC on the three prescriptions in IS with QDBS syndromes, find the biomarkers that can serve as objective indicators of IS with QDBS syndromes, thus to provide objective basis for precise treatment of TCM, and improve clinical effect. This is a multicentre, randomized, double-blinded, positive and placebo-controlled intervention trial of IS with QDBS syndromes, followed by an add-on of Chinese patent medicine. A total of 160 participants will be randomly assigned to the BHG, NXTC, YTG, and placebo groups in a 1:2:1:1 allocation ratio. All participants will receive a 28-day treatment and then be followed-up for another 180 days. The primary outcome is the changes of NIHSS score28 days after medication. The secondary outcomes include Modified Rankin scale (mRS) scores, Activity of daily living (ADL) scale scores, TCM symptom scores. Data will be analyzed in accordance with a predefined statistical analysis plan. Ethical approval of this trial has been granted by the Research Ethics Committee of the First Affiliated Hospital of Zhejiang Chinese Medical University (ID: 2017-Y-004-02). Written informed consent will be obtained from all participants. This trial is registered in the Chinese Clinical Trial Registry (ChiCTR1800015189), and the results will be disseminated to the public through academic conferences and peer-reviewed journals.